Hunger games - Collins, Suzanne (London Scholastic, 2008)
By winning the annual Hunger Games, District 12 tributes Katniss Everdeen and Peeta Mellark have secured a life of safety and plenty for themselves and their families, but because they won by defying the rules, they unwittingly become the faces of an impending rebellion.
Keywords: Insurgency -- Juvenile fiction; Survival -- Juvenile fiction; Television programs -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Contests -- Juvenile fiction; Dystopias -- Juvenile fiction